Industry-Based Economic Education Curriculum 4.0 In Vocational High Schools - Hariyono Hariyono (Publikasi Indonesia, 2023)
Industry 4.0-based economic education in Vocational High Schools (SMK) aims to produce graduates who have skills that are in accordance with the demands of the job market. This journal article discusses the curriculum for Industry 4.0-based economic education in SMK, theoretical studies of Industry 4.0 and its influence on economic education, as well as the stages of curriculum implementation, obstacles in implementation, and solutions to overcome them. This article uses a descriptive method of analysis by collecting data from various sources and conducting qualitative analysis of the data. The results showed that the Industry 4.0-based economic education curriculum can provide excellence in preparing SMK students to become a workforce that is ready to face the challenges of Industry 4.0. However, there are obstacles in curriculum implementation, such as limited resources and lack of teacher knowledge in using technology. Solutions to overcome these obstacles include increasing resources, providing training to teachers, and optimizing the use of technology in learning. Therefore, the development of an Industry 4.0-based economic education curriculum in SMK needs to continue to be carried out by taking into account the challenges and needs of the job market.